A study of the educational system of Malaya - Manalaysay, Raquel Salting 1921- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1954)
The educational system of Malaya is the subject of this study. Included in this study are: the territorial constitution of Malaya, its historical background, the foundation of its educational system, the administration and organization of such a system, the various educational levels-- primary, secondary, post-secondary and university education, the provision for teacher training, and some problems confronting the education in Malaya.